Environmental Impacts and Their Association With Performance and Excretion Traits in Growing Pigs - Monteiro, Alessandra N. T. R.; Brossard, Ludovic; Gilbert, Hélène; Dourmad, Jean-Yves (Frontiers in Veterinary Science, 2021)
The selection of pigs for improved production traits has been, for a long time, the major driver of pig breeding. More recently, because of the increasing concern with the environment, new selection criteria have been explored, such as nitrogen (N) excretion. However, many studies indicate that life cycle assessment (LCA) provides much better indicators of environmental impacts than excretion. Therefore, the objective of this study was to investigate, using a modelling approach, the relationships between production traits and LCA impacts of individual growing pigs calculated at farm gate for one kg of body weight. Performances of pigs were simulated for 2-phase (2P) and precision feeding (PR), using InraPorc population model (on 1,000 pigs). Nitrogen excretion was positively correlated with feed conversion ratio (FCR; r = +0.96), climate change (CC; r = +0.96), acidification potential (AC; r = +0.97), eutrophication potential (EU; r = +0.97), and land occupation (LO; r = +0.96), whatever the feeding program. However, FCR appeared a better indicator of LCA impacts, with very high and positive correlations (r > +0.99) with CC, AC, EU, and LO for both feeding programs. The CC, AC, and EU impacts of pig production for PR feeding were 1.3, 10 and 7.5% lower than for 2P, respectively, but the correlations within each outcome were very similar among feeding programs. It was concluded that the use of FCR as a selection criterion in pig breeding seems a promising approach to associate improved performance and low environmental impact of pig fattening.